Fuzzy Multi-criteria Decision-Making Using Neutrosophic Sets - Kahraman, Cengiz; Otay, İrem.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book offers a comprehensive guide to the use of neutrosophic sets in multiple criteria decision making problems. It shows how neutrosophic sets, which have been developed as an extension of fuzzy and paraconsistent logic, can help in dealing with certain types of uncertainty that classical methods could not cope with. The chapters, written by well-known researchers, report on cutting-edge methodologies they have been developing and testing on a variety of engineering problems. The book is unique in its kind as it reports for the first time and in a comprehensive manner on the joint use of neutrosophic sets together with existing decision making methods to solve multi-criteria decision-making problems, as well as other engineering problems that are complex, hard to model and/or include incomplete and vague data. By providing new ideas, suggestions and directions for the solution of complex problems in engineering and decision making, it represents an excellent guide for researchers, lecturers and postgraduate students pursuing research on neutrosophic decision making, and more in general in the area of industrial and management engineering.
A State-of-The-Art Review of Neutrosophic Sets & Theory -- Arithmetic Operations of Neutrosophic Sets, Interval Neutrosophic Sets and Rough Neutrosophic Sets -- Power Harmonic Weighted Aggregation Operator on Single-Valued Trapezoidal Neutrosophic Numbers and Interval-Valued Neutrosophic Sets -- Linear and Non-linear Neutrosophic Numbers -- Bipolar Neutrosophic Graphs -- Three-way Bipolar Neutrosophic Concept Lattice -- Interval-Valued Neutrosophic Numbers with WASPAS -- Interval Neutrosophic Sets with TODIM Method -- Multiple attribute Projection Methods with Neutrosophic Sets -- Bipolar Complex Neutrosophic Sets and its Application in Decision Making Problem -- Development of Fuzzy Single Valued Neutrosophic MADM Technique to Improve Performance in Manufacturing and Supply Chain Functions.
Keywords: Computational intelligence; Industrial Management; Operations research; Management science; Computational Intelligence; Industrial Management; Operations Research, Management Science; Operations Research and Decision Theory